Ultrasonic aerosol agglomeration: manipulation of particle deposition and its impact on air filter pressure drop - Liu, Pengzhan (2024)
Acoustic agglomeration is a technique that leverages on sound waves to promote the collision of aerosol particulate matter, thus leading to the formation of larger particle agglomerates. In this study, this acoustics-driven phenomenon is demonstrated for its usefulness as an aerosol pre-conditioning method to significantly enhance the efficiency of filtration systems in particle treatment processes. Specifically, favorable changes in pressure drop across the filters are observed as a result of receiving less particle mass, for which filters are shown to be able to have their operational life extended remarkably by more than 50%. The involved ultrasonic aerosol agglomeration mechanisms are unveiled through numerical simulations, and the effects of residence time, sound pressure level, and initial particle number concentration on agglomeration performances are experimentally investigated. In addition, validations and measurements of filter pressure drop are obtained through a series of experiments. This study provides a comprehensive overview to the design and performance characterization of acoustics-agglomeration-enhanced filtration systems, which could potentially derive energy savings for fan power in ventilation systems and be scaled up for applications in industrial plants for reducing carbon emissions.